c = 2d−5−bad
c = 2d−5−abdad
c = 2d−5−abad
c = 5−2d−bad
Correct answer is B
a(b + c) + 5d - 2 = 0
ab + ac + 5d - 2 = 0
abd + acdd + 5 - 2 = ab + ac + 5 - 2d
acd = 2d - 5 - abd
c = 2d−5−abdad
A chord of a circle radius √3cm subtends an angle of 60° on the circumference of ...
If y varies directly as √n and y = 4 when n = 4, find y when n = 179...
Make y the subject of the formula Z = x2 + 1y3...
Divide the sum of 8, 6, 7, 2, 0, 4, 7, 2, 3, by their mean ...
In the diagram above. |AB| = 12cm, |AE| = 8cm, |DCl = 9cm and AB||DC. Calculate |EC| ...
Solve for (x, y) in the equation 2x + y = 4: x^2 + xy = -12...